Membangun Motivasi dalam Pembelajaran Matematika Berbasis Media Wordwall: Studi Komparatif tentang Motivasi Model ARCS dan Perspektif Gender di Kalangan Siswa Sekolah Menengah Atas di Lebak-Banten - Yulianto, Dwi; Juniawan, Egi Adha; Junaedi, Yusup; Anwar, Syahrul; Umami, Moh Rizal (SJME (Supremum Journal of Mathematics Education), 2024)
This research is motivated by concerns about low student motivation in the educational environment. The main objectives of this study are: 1) to understand the level of motivation among the majority of high school students in Lebak Banten Regency in learning mathematics using the Wordwall media; 2) to explore differences in the level of student motivation based on the ARCS model in mathematics learning utilizing the Wordwall media, considering sex factors; 3) to analyze the percentage of each ARCS aspect contributing to the level of motivation in mathematics learning using the Wordwall media; 4) to identify how the percentage of each ARCS aspect affects the level of motivation in mathematics learning using the Wordwall media, considering sex differences; 5) to examine the influence of Wordwall-based mathematics learning on sex-based motivation seen from the ARCS model. The research method used is quantitative with a quasi-experimental approach and a One-Group Pretest-Posttest research design. The data analysis results show that female students' motivation tends to be higher than that of male students, with the motivation percentage of female students being higher in each aspect of ARCS motivation. The Satisfaction aspect has the highest percentage, which is 78.53%. There is a significant increase in the motivation of male and female students from pretest to posttest. The increase is seen in all four aspects of ARCS motivation. In male students, there is an increase from an average of 47.36% to 75.00%, while in female students, there is an increase from 54.25% to 83.16%. Additionally, there is an influence before and after Wordwall-based mathematics learning based on sex seen from the ARCS model